The Efficacy of Cognitive Videogame Training for ADHD and What FDA Clearance Means for Clinicians. Issue 1 (2nd January 2021) - Evans, Steven W.; Beauchaine, Theodore P.; Chronis-Tuscano, Andrea; Becker, Stephen P.; Chacko, Anil; Gallagher, Richard; Hartung, Cynthia M.; Kofler, Michael J.; Schultz, Brandon K.; Tamm, Leanne; Youngstrom, Eric A.
ABSTRACT: News of a videogame that received FDA clearance to treat youth with attention-deficit hyperactivity disorder (ADHD) garnered a great deal of media attention and raised questions about the role of digital cognitive training programs for treatment. In order for clinicians and clients to understand this news for the purposes of making treatment decisions one must have an understanding of what it means for a treatment to be considered evidence-based and an understanding of what is required to obtain FDA clearance. Finally, in order to fully inform decisions about treatment, clinicians and parents must be able to consider the evidence supporting cognitive training programs in relation to other treatments available for children with ADHD. A review of these standards and the evidence supporting cognitive training in general, and the new videogame that received recent FDA clearance (EndeavorRX TM ) specifically, revealed an overall lack of support for this approach to treatment. There are multiple psychosocial and pharmacological treatment options with much more evidence supporting their effectiveness than any commercially available cognitive training program. The contrast between receiving FDA clearance without evidence of any observable benefits to the child is explained within a description of the FDA process for clearance and approval. Finally, these conclusions are described in the context of clinicians' decisions regarding services offered and procedures for explaining this to families who may have seen the media attention related to FDA clearance.